Synergistic effects of cattle dung, urea and lime on agronomic productivity and physicochemical properties of coarse-textured tropical soils - Ameh, Precious I.; Etukudo, Ntieneobong E.; Joseph, Paul O.; Onuze, Benjamin A.; Ndzeshala, Solange T.; Isaac, Blessing I.; Obalum, Sunday E.; Baiyeri, Kayode P.; Igwe, Charles A. (Journal of Agriculture and Environment for International Development (JAEID), 2025)
A major limitation to the use of some biowaste as manure is their high C/N ratio and hence slow mineralisation rate. Combined use of such slow-mineralising animal manures with N-rich fertilizers and/or synthetic lime may valorize them. The objective of this study was to assess the synergistic effects of cattle dung (CD), Urea and lime on crop productivity and physicochemical properties of sandy tropical soils. Treatments of CD, Urea, Lime, CD+Urea, CD+Lime, Urea+Lime, CD+Urea+Lime, standardized CD+Urea and Control were used to grow okra on sandy soils from a long-term fallow land. The CD and Lime were added at 20 and 0.15-t/ha equivalents three weeks before okra sowing, and Urea at 5-t/ha equivalent at sowing except for standardized CD+Urea where this mix (with reduced C/N of ca.10) was added three weeks before sowing. Agronomic and soil data were collected during and after nine-week crop growth phase, respectively. Treatment affected okra growth and soil variables. Plant height and leaf area generally showed CD+Urea+Lime > CD+Urea/CD+Lime/CD > Urea+Lime/Control, with 56-81% and 124-125% increases, respectively in CD+Urea+Lime relative to Urea+Lime/Control. However, CD+Urea and Urea+Lime/Urea/Lime/Control produced the most and fewest leaves per plant, respectively. Treatment CD+Urea+Lime gave the highest okra dry matter, lowest soil bulk density and highest available P and cations exchange. The CD+Lime improved macro-aggregation the most but, together with standardized CD+Urea, also caused soil colloidal dispersion. Okra dry matter reflected soil available P (R2 = 0.63). Fortifying CD-manure with lime and, afterward, Urea could produce synergistic agronomic effects mostly via boosted P-bioavailability, and is hereby proposed for physicochemical fertility management of coarse-textured acid tropical soils.